Activation of Stimulator of IFN Genes (STING) Causes Proteinuria and Contributes to Glomerular Diseases. Issue 12 (December 2022) - Mitrofanova, Alla; Fontanella, Antonio; Tolerico, Matthew; Mallela, Shamroop; Molina David, Judith; Zuo, Yiqin; Boulina, Marcia; Kim, Jin-Ju; Santos, Javier; Ge, Mengyuan; Sloan, Alexis; Issa, Wadih; et al.
Significance Statement: A signaling molecule that plays a role in the innate immune system, stimulator of IFN genes (STING), is a crucial regulator of the cyclic GMP-AMP synthase (cGAS)-STING pathway. This signaling pathway regulates inflammation and energy homeostasis under conditions of obesity, kidney fibrosis, and AKI, but its exact role in the pathogenesis of glomerular diseases remains unclear. The authors found that activation of STING in wild-type mice is sufficient to cause albuminuria and podocyte loss, and that the cGAS-STING signaling pathway is upregulated in mice with experimental diabetic kidney disease and Alport syndrome. They also demonstrated that either genetic or pharmacologic STING inhibition confers protection from kidney disease progression. These findings suggest that this signaling pathway plays an important role in mediating glomerular dysfunction. Visual Abstract: Abstract : Background: The signaling molecule stimulator of IFN genes (STING) was identified as a crucial regulator of the DNA-sensing cyclic GMP-AMP synthase (cGAS)-STING pathway, and this signaling pathway regulates inflammation and energy homeostasis under conditions of obesity, kidney fibrosis, and AKI. However, the role of STING in causing CKD, including diabetic kidney disease (DKD) and Alport syndrome, is unknown. Methods: To investigate whether STING activation contributes to the development and progression of glomerular diseases such as DKD and Alport syndrome, immortalized human and murine podocytes were differentiated for 14 days and treated with a STING-specific agonist. We used diabetic db/db mice, mice with experimental Alport syndrome, C57BL/6 mice, and STING knockout mice to assess the role of the STING signaling pathway in kidney failure. Results: In vitro, murine and human podocytes express all of the components of the cGAS-STING pathway. In vivo, activation of STING renders C57BL/6 mice susceptible to albuminuria and podocyte loss. STING is activated at baseline in mice with experimental DKD and Alport syndrome. STING activation occurs in the glomerular but not the tubulointerstitial compartment in association with autophagic podocyte death in Alport syndrome mice and with apoptotic podocyte death in DKD mouse models. Genetic or pharmacologic inhibition of STING protects from progression of kidney disease in mice with DKD and Alport syndrome and increases lifespan in Alport syndrome mice. Conclusion: The activation of the STING pathway acts as a mediator of disease progression in DKD and Alport syndrome. Targeting STING may offer a therapeutic option to treat glomerular diseases of metabolic and nonmetabolic origin or prevent their development, progression, or both.